1971
DOI: 10.1139/v71-265
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Attack of Siloxycarbenes on Carbonyl Groups. The Formation of Oxiranes

Abstract: Siloxycarbenes, formed by the photolysis of dimethyl- or diphenylsilacyclohexanone have been trapped as oxiranes or as the ring-opened hydrolysis products of oxiranes, with simple aldehydes and ketones such as acetaldehyde, or cyclohexanone. The reactions are interpreted as arising from the nucleophilic attack of the siloxycarbene on the carbonyl group. The structures of the oxiranes and their hydrolysis products have been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…This result prompted us to develop photoinduced cross benzoin‐type reaction for preparation of α‐hydroxyketones by utilizing siloxycarbenes as an acyl anion equivalent. Although a closely related work has been already reported by Brook and co‐workers, the reaction was limited only to 2‐silacyclohexanone 3 as an acylsilane unit (Scheme , equation b) . Thus, intermolecular coupling of readily available acyclic acylsilanes with aldehydes remains unexplored.…”
Section: Methodsmentioning
confidence: 99%
“…This result prompted us to develop photoinduced cross benzoin‐type reaction for preparation of α‐hydroxyketones by utilizing siloxycarbenes as an acyl anion equivalent. Although a closely related work has been already reported by Brook and co‐workers, the reaction was limited only to 2‐silacyclohexanone 3 as an acylsilane unit (Scheme , equation b) . Thus, intermolecular coupling of readily available acyclic acylsilanes with aldehydes remains unexplored.…”
Section: Methodsmentioning
confidence: 99%
“…the effectiveness of trapping agents would depend either on their proton donating or electron donating ability. Evidence has already been published which demonstrated that cyclic siloxycarbenes from silacyclohexanones were strongly nucleophilic in nature, forming a cyclopropane adduct with the electron-deficient olefin, diethyl fumarate (9), or oxiranes via nucleophilic attack of the carbonyl group of aldehydes and ketones (10). The photochemistry of the acyclic acylsilanes (none of which were found to form related cyclopropanes or oxiranes in detectable amounts) is also most readily interpreted on the basis of the siloxycarbene being markedly nucleophilic.…”
Section: The Mechanism Of Formation Of the Mixed Acetals And Related mentioning
confidence: 99%
“…4, 70.5 (24 C(2'), C(4')); 141.0 (s, C (3)). MS: 218 (1 1, M +, C,5H,20), 203 (22), 177 (16), 175(12), 162(36), 161 (26), 159(11), 147(40), 145(20), 135 (15), 134(15), 133(25), 131 (lo), 123(36), 121 (49, 120 (18), 119(90), 117 (13), 109 (12), 108 (15), 107(46), 106(26),105(100),95 (24),93(35),91 (55),81 (23),80(11),79 (38),77 (39,69 (IS),67 (39,65 (19), 57 (II), 55 (33), 53 (22), 51 (12) (23,000). IR: 3085m, 3005s, 2962s, 2934s, 2920s, 2875m, 2850m, 1780w (br.…”
Section: Experimental Partmentioning
confidence: 99%
“…"C-NMR: 18.6, 20.0, 28.1, 28.9 (4q, 4 CH,); 9.6 (1, C(8')); 34.3 (t, C(6')); 116.5 (t. C(4)); 11.5, 15.4 (24 C(l'), C(7')); 127. 5,135.9 (24 C(l), C(2)); 33.2 (s, C(5')); 67.4,70.2 (2s, C(2'), C(4')); 140.8 (12), 108 (13), 107 (42), 106 (25), 105(100), 95 (21), 93 (35), 92 (IS), 91 (60), 81 (20), 80 (II), 79 (41), 78 (lo), 77 (36), 69 (14). 67 (31), 65 (19).…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation